Smelling like a man : a socio-olfactory analysis of masculinity in Singapore. - Nur Amin Shah Hashim. (2012)
This exploratory study investigates the impacts of smell upon masculinity. Based on participant observations, surveys and in-depth narrative interviews, I extend to the theories of hegemonic masculinity (Connell 2005) and gender performativity (Butler and Salih 2004) in providing an olfactory dimension. I organized my discussion around three themes that smell(s) i) is an embodied phenomenon, which influences gender performativity of those studied, ii) are appropriated through discursive practices that reveal power relations in various contexts and, iii) not only reproduces gender performativity but provides alternative channels for reconstructing gender perceptions. By examining the perceptions of smells among males in Singapore, this paper will attempt to elucidate the multiplicities of masculinities evident in various contexts.